A review on enhancing higher education access for rural students through university high-impact community engagement programs in Malaysia - Wan Hamdan, Wan Samsul Zamani; Abdul Rahman, Nor Azalina Yusnita; Ahmad, Nur Azfahani; Mohd Radzuan, Nor Amin; Aziz, Nor Diana (Universiti Teknologi MARA, Kedah, 2024)
This study investigates the decline in higher education applications among rural secondary school students in Malaysia, exacerbated by educational disparities and the impact of the COVID-19 pandemic. Rural students face significant challenges, including limited access to modern educational facilities, technology, and experienced teachers, which contributes to lower academic performance compared to their urban peers. Additionally, economic hardships and disruptions from the pandemic have further discouraged rural students from pursuing higher education. The study examines how High-Impact Community Engagement (HICE) activities and Educational Knowledge Transfer Programs (KTP) can address these issues. By facilitating mentorship programs, community workshops, and industry collaborations, HICE initiatives aim to bridge the educational gap and support rural students. KTPs enhance this by providing access to digital resources, teacher training, and financial aid. The research utilizes a systematic review methodology to assess the effectiveness of these programs and propose strategic recommendations for improving rural education. The findings suggest that well-implemented community engagement and knowledge transfer can significantly increase higher education applications and academic performance among rural students. The study emphasizes the importance of collaborative efforts between educational institutions, local communities, and industries to overcome existing barriers and promote educational equity in Malaysia.